Protection of surface states in topological nanoparticles - Siroki,G; Haynes,PD; Lee,DKK; Giannini,V (Physical Review Materials, 2017)
opological insulators host protected electronic states at their surface. These states show little sensitivity todisorder. For miniaturization one wants to exploit their robustness at the smallest sizes possible. This is alsobeneficial for optical applications and catalysis, which favor large surface-to-volume ratios. However, it is notknown whether discrete states in particles share the protection of their continuous counterparts in large crystals.Here we study the protection of the states hosted by topological insulator nanoparticles. Using both analyticaland tight-binding simulations, we show that the states benefit from the same level of protection as those on aplanar surface. The results hold for many shapes and sustain surface roughness which may be useful in photonics,spectroscopy, and chemistry. They complement past studies of large crystals—at the other end of possible lengthscales. The protection of the nanoparticles suggests that samples of all intermediate sizes also possess protectedstates.